Dynamics and ecological reassembly of the human gut microbiome and the host metabolome in response to prolonged fasting - Sang, Xiaopu; Li, Shenghui; Guo, Ruochun; Yan, Qiulong; Liu, Changxi; Zhang, Yue; Lv, Qingbo; Wu, Lili; Ma, Jie; You, Wei; Feng, Ling; Sun, Wen (Frontiers in Microbiology, 2023)
Prolonged fasting is an intervention approach with potential benefits for individuals with obese or metabolic disorders. Changes in gut microbiota during and after fasting may also have significant effects on the human body. Here we conducted a 7-days medically supervised water-only fasting for 46 obese volunteers and characterized their gut microbiota based on whole-metagenome sequencing of feces at five timepoints. Substantial changes in the gut microbial diversity and composition were observed during fasting, with rapid restoration after fasting. The ecological pattern of the microbiota was also reassembled during fasting, reflecting reduced metabolic capacity of diet-derived carbohydrates, while other metabolic abilities such as degradation of glycoproteins, amino acids, lipids, and organic acid metabolism, were enhanced. We identified a group species that responded significantly to fasting, including 130 fastingresistant (consisting of a variety of members of Bacteroidetes, Proteobacteria, and Fusobacteria) and 140 fasting-sensitive bacteria (mainly consisting of Firmicutes members). Functional comparison of the fastingresponded bacteria untangled the associations of taxon-specific functions (e.g., pentose phosphate pathway modules, glycosaminoglycan degradation, and folate biosynthesis) with fasting. Furthermore, we found that the serum and urine metabolomes of individuals were also substantially changed across the fasting procedure, and particularly, these changes were largely affected by the fasting-responded bacteria in the gut microbiota. Overall, our findings delineated the patterns of gut microbiota alterations under prolonged fasting, which will boost future mechanistic and clinical intervention studies.